ANALISIS RENCANA PENERAPAN SISTEM INFORMASI MANAJEMEN KOPERASI SIMPAN PINJAM DI KOPERASI PEKERJA POS INDONESIA - Said Bambang Nurcahya; Kunto Ajibroto; Riffka Fauzany; Gina Legiana (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2022)
State-Owned Enterprises are companies whose capital and ownership are owned by the State aimed at fulfilling the welfare of the community in various business fields, BUMN operations are supervised, controlled, and controlled by the State to serve the public interest and public services, so that they can be used as sources of state income with the risk of business activities. borne by the government, as for the products needed by the community, currently SOEs are made into clusters including tourism and support services, telecommunications and media clusters, energy, oil and gas clusters, health clusters, manufacturing clusters, mineral and coal clusters, food clusters and fertilizers, and plantation and forestry clusters. Pos Indonesia is a limited liability company in the service of dividing into six regions or regional divisions with divisions covering all provinces divided into 6 regions. PT Pos Indonesia itself is headquartered on Jl. Banda No. 20 Bandung City, West Java, with a total of 23,825 employees in 2019, at PT. Pos Indonesia there are several PT Pos Indonesia unions including the Indonesian Postal Workers Cooperative (KOPPIN). KOPPIN has a business in the field of financial institutions in the form of employee/worker cooperatives. In order to transform digital services, KOPPIN implements a savings and loan cooperative management information system. For this reason, the analysis starts from Information Technology infrastructure, analysis of the Savings and Loans Management Information System and analysis of the Cooperative Accounting Information System, so that the application application is in accordance with the needs. Keywords: Analysis, Application of Information Systems, Savings and Loan Management, Cooperative Accounting